THE ARTERIAL STIFFNESS IS INFLUENCED BY THE HEMOSTATIC SYSTEM IN NON-DIABETIC HYPERTENSIVE PATIENTS. (June 2018) - Catena, C.; Colussi, G.; Brosolo, G.; Bertin, N.; Frangipane, A.; Nait, F.; Sechi, L.A.
Abstract : Objective: In the general population an increased arterial stiffness is associated with a high risk of cardiovascular events. In essential hypertension high plasma fibrinogen and D-dimer levels are associated with cardiovascular damage. The aim of this study was to search for a relationship between indexes of activation of the coagulation system and parameters of arterial stiffness, such as the pulse wave velocity (PWV) and the augmentation index (AIx), in essential hypertensive patients without diabetes or renal failure. Design and method: In 76 hypertensive patients (age 52 ± 14 y; 35 male; 30 never treated with antihypertensive drugs) we evaluated clinical and anthropometric variables, plasma level of glucose, lipids, fibrinogen and D-dimer, and creatinine clearance, PWV e AIx. Results: Patients were subdivided into tertiles of PWV. Patients with higher PWV were older, more frequently males, had a greater percentage of antihypertensive drugs, a greater alcohol consumption, and higher fibrinogen e D-dimer levels than in patients with lower PWV. At univariate analysis the PWV was significantly and directly related to age, BMI, systolic pressure, duration of hypertension, alcohol intake, plasma levels of glucose, fibrinogen (r = 0.369, P = 0.001) and D-dimer (r = 0.390, P < 0.001). The PWV was higher in males than females (P = 0.036) and in previously treated patients than in naive subjects (P = 0.003). At multivariate analysis including PWV as the dependent variable, PWV was independently associated with age (beta = 0.310, P = 0.015) and D-dimer levels (beta = 0.222, P = 0.049). At univariate analysis AIx was significantly and directly related to age, total and LDL-cholesterol, fibrinogen (r = 0.349, P = 0.002), and inversely related to diastolic pressure, and it was higher in previous treated than in never treated patients. At multivariate analysis AIx was independently associated with age (beta = 0.235, P = 0.048) and LDL-cholesterol (beta = 0.328, P = 0.003). Conclusions: This study supports the hypothesis of an association of a prothrombotic state with the vascular damage of hypertension that might contribute to the cardiovascular risk in these patients.